A REVIEW OF THE MONOGRAPH “SIDE EFFECTS OF ANTI-EPILEPTIC THERAPY” BY O.A. PYLAEVA, K.YU. MUKHIN, A.S. PETRUKHIN (Moscow: GRANAT, 2016. 232 p.) - S. K. Evtushenko (Русский журнал детской неврологии)
.